The Effects of Aquatic Plyometric Training on Repeated Jumps, Drop Jumps and Muscle Damage - Jurado-Lavanant, A.; Alvero-Cruz, J. R.; Pareja-Blanco, F.; Melero-Romero, C.; Rodríguez-Rosell, D.; Fernandez-Garcia, J. C. (International Journal of Sports Medicine, 2018)
The purpose of this study was to compare the effects of land- vs. aquatic based plyometric training programs on the drop jump, repeated jump performance and muscle damage. Sixty-five male students were randomly assigned to one of 3 groups: aquatic plyometric training group (APT), plyometric training group (PT) and control group (CG). Both experimental groups trained twice a week for 10 weeks performing the same number of sets and total jumps. The following variables were measured prior to, halfway through and after the training programs: creatine kinase (CK) concentration, maximal height during a drop jump from the height of 30 (DJ30) and 50 cm (DJ50), and mean height during a repeated vertical jump test (RJ). The training program resulted in a significant increase (P<0.01–0.001) in RJ, DJ30, and DJ50 for PT, whereas neither APT nor CG reached any significant improvement APT showed likely/possibly improvements on DJ30 and DJ50, respectively. Greater intra-group Effect Size in CK was found for PT when compared to APT. In conclusion, although APT seems to be a safe alternative method for reducing the stress produced on the musculoskeletal system by plyometric training, PT produced greater gains on reactive jumps performance than APT.
Keywords: vertical jump; stretch-shortening cycle exercise; muscle strength; muscle soreness; creatine kinase; reactive jumps